The influence of Healozone on microleakage and fissure penetration of different sealing materials - Dukić, Walter (Array, 2009)
Abstract: The preventive effect of sealing materials depends on ability to penetrate into the fissures, and microleakage absence, resulting with better clinical success. The aim of present study was to investigate the influence of ozone on microleakage and penetration of nanoparticle fissure sealing resin and flowable composite, and quantitative and qualitative analysis of microleakage. Forty extracted non carious third molars were randomly divided in 4 groups. Group A: KaVo Healozone and Grandio Seal; Group B: Kavo Healozone and X-Flow; Group C: Grandio Seal; Group D: X-Flow. The teeth were thermocycled, immersed in 5% methylene dye for 24 hours, and sectioned with precision saw. The total of 149 slices were analysed with stereomicroscope for microleakage and sealant penetration. According to qualitative scores, there is a significant difference between groups C and D, group C showing better results. According to quantitative scores, there are no statistical differences between the groups. The treatment of the enamel with KaVo HealOzone after etching does not affect either microleakage or penetration proportion of flowable composite or sealing resin. There is no statistically significant difference in a degree of penetration between different groups of sealing materials. Groups of materials with flowable composite in combination with an adhesive system show a good degree of penetration into the fissure and low microleakage meaning that they can be used as a fissure sealing materials